3D-printable self-healing and mechanically reinforced hydrogels with host–guest non-covalent interactions integrated into covalently linked networks. Issue 4 (9th January 2019) - Wang, Zhifang; An, Geng; Zhu, Ye; Liu, Xuemin; Chen, Yunhua; Wu, Hongkai; Wang, Yingjun; Shi, Xuetao; Mao, Chuanbin
Abstract : Novel 3D-printable hydrogels with host–guest non-covalent interactions and covalently crosslinked networks show robust mechanical strength, self-healing performance and excellent biocompatibility. Abstract : Natural polymer hydrogels are one of the best biomaterials for soft tissue repair because of their excellent biocompatibility, biodegradability and low immune rejection. However, they lack mechanical strength matching that of natural tissue and desired functionality ( e.g., self-healing and 3D-printability). To solve these problems, we developed a host–guest supramolecule (HGSM) with three arms covalently crosslinked with a natural polymer to construct a novel hydrogel with non-covalent bonds integrated into a covalently crosslinked network. This unique structure enabled the hydrogel to exhibit improved mechanical properties and show both self-healing and 3D printing capabilities. The three-armed HGSM was first prepared via efficient non-covalent host–guest inclusion interactions between isocyanatoethyl acrylate-modified β-cyclodextrin (β-CD-AOI2 ) and acryloylated tetra-ethylene glycol-modified adamantane (A-TEG-Ad). Subsequently, a host–guest supramolecular hydrogel (HGGelMA) was obtained through copolymerization between the arms of the HGSM and gelatin methacryloyl (GelMA) to form a covalently crosslinked network. The HGGelMA was robust, fatigue resistant, reproducible and rapidly self-healing. In the HGGelMA, the covalent crosslinking maintained its overall shape, whereas the weak reversible non-covalent host–guest interactions reinforced its mechanical properties and enabled it to rapidly self-heal upon fracturing. The reversible non-covalent interactions could be re-established upon breaking, so as to heal the hydrogel and dissipate energy to prevent catastrophic fracture propagation. Furthermore, the precursors of the HGGelMA were sufficiently viscous and could be rapidly photocrosslinked to produce a robust scaffold with an exquisite internal structure through 3D printing. The 3D-printed HGGelMA hydrogel scaffold was biocompatible, promoted cell adhesion and proliferation, and supported tissue in-growth. Our strategy of integrating a non-covalently linked HGSM into a covalently linked hydrogel network represents a new approach to the development of natural polymers into biocompatible hydrogels with improved strength as well as desired self-healing and 3D-printability.